Activating cultural and social change
1 online resource.
Keywords: "In this thought-provoking book, a diverse range of educators, activists, academics, and community advocates provide theoretical and practical ways of activating our knowledge and understanding of how to build a human rights culture. Addressing approaches and applications to human rights within current socio-cultural, political, socio-legal, environmental, educational, and global contexts, these chapters explore tensions, contradictions, and complexities within human rights education. The book establishes cultural and educational practices as intrinsically linked to human rights consciousness and social justice, showing how signature pedagogies used by human rights practitioners can be intellectual, creative, or a combination of both. Across three sections, the book discusses ways of bringing about holistic, relevant, and compelling approaches for challenging and understanding structures of power, which have become a global system, while also suggesting a move from abstract human rights principles, declarations, and instruments to meaningful changes that do not dehumanise and distance us from intrinsic and extrinsic oppressions, denial of identity and community, and other forms of human rights abuse. Offering new critical cultural studies approaches on how a human rights consciousness arises and is practised, this book will be of great interest to scholars and students of cultural studies, education studies, critical sociology, human rights education, and human rights studies"--